Reduction of microkinetic reaction models for reactor optimization exemplified for hydrogen production from methane - Karst, Florian; Maestri, Matteo; Freund, Hannsjörg; Sundmacher, Kai (Chemical Engineering Journal, 2015)
Sustainable and efficient processes require optimal design and operating conditions. The determination of optimal process routes, however, is a challenging task. Either the models and underlying chemical reaction rate equations are not able to describe the process in a wide ranges of reaction conditions and thus limit the optimization space, or the models are too complex and numerically challenging to be used in dynamic optimization. To address this problem, in this contribution, a reduction technique for chemical reaction networks is proposed. It focuses on the sensitivity of the reaction kinetic model with respect to the removal of selected reaction steps and evaluates their significance for the prediction of the overall system behavior. The method is demonstrated for a C-1 microkinetic model describing methane conversion to syngas on Rh/Al2O3 as catalyst. The original and the reduced microkinetic model show excellent qualitative and quantitative agreement. Subsequently, the reduced kinetic model is used for the optimization of a methane reformer to produce a hydrogen rich gas mixture as feed for polymer electrolyte membrane (PEM) fuel cell applications. (C) 2015 The Authors. Published by Elsevier B.V.
Keywords: Microkinetic modeling; Reactor optimization; Reaction networks; Methane conversion; Process design